Titi INFLUENCES OF BRAND EXPERIENCE, BRAND TRUST, AND BRAND LOVE TOWARD PURCHASE INTENTION BY WORD OF MOUTH AND BRAND LOYALTY AS INTERVENING VARIABLES IN FASHION BRANDED IN EAST SURABAYA - Sukarman, Titi Murtiningsih (Archives of Business Research, 2019)
The fashion industrial growth is seen from many and many retail shops and modern shopping centers that emerge, especially Surabaya city. Brand has special emotional bond created between consumers and company, so consumer love toward some brand will give positive impacts. This research aims to know influences of brand experience, brand trust, and brand love toward purchase intention by word of mouth and brand loyalty as intervening variables in fashion branded in East Surabaya. The approach used is quantitative method by causal research type. The research samples are fashion branded users of Nike brand in East Surabaya as 190 respondents. The instruments used are questionnaires by using Likert scale. The analysis technique chosen for analyzing data and testing hypothesis in this research The Structural Equation Model (SEM). The research results show that Brand Experience and Brand Trust influence toward Word of Mouth in Fashion Branded in East Surabaya. Brand Experience does not influence significantly but it has positive influence directions toward Purchase Intention in Fashion Branded in East Surabaya. Brand Experience influences toward Brand Loyalty in Fashion Branded in East Surabaya. Brand Trust influences toward Purchase Intention in Fashion Branded in East Surabaya. Brand Trust does not influence significantly but it has positive influences toward Brand Loyalty in Fashion Branded in East Surabaya. Brand Love does not influence significantly but it has positive influence directions toward Word of Mouth in Fashion Branded in East Surabaya. Brand Love does not influence significantly but it has positive influence directions toward Purchase Intention in Fashion Branded in East Surabaya. Brand Love does not influence toward Brand Loyalty. Word of Mouth and Brand Loyalty influence toward Purchase Intention in Fashion Branded in East Surabaya.